Five Year Experience of Breast Cancer Surgeries - Ammarah Afzal, Khushbakht Ali Khan, Bilal Chaudhary, Laiq Folad, Ali Akbar Subhani, Umair Sohail Mehr (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To audit the breast cancer surgeries and to establish the age groups and stage at which breast cancer patients present in our institution. Study design: Retrospective study Place and duration of study: Department of Surgery, Jinnah Hospital, Lahore from January 1st 2017 to December 31st 2021. Methodology: Four hundred and seventy-one breast cancer patients were sorted out. The data included the stage of presentation of breast cancer, age at presentation, year of presentation, gender and surgeries performed according to stage of carcinoma of breast. Results: The patient of breast carcinoma usually presents for medical help in her forties (31%) while patients presented between 18 to 86 years of age. Most patients however presented in stage III. Frequent sentinel lymph node biopsies with breast conservation surgery. All stage III breast carcinoma patients were treated with MRM and level II axillary clearance. BCS with sentinel lymph node biopsy was done for early breast cancer. Conclusion: Carcinoma of breast presents in earlier age in Pakistan as compared to West. Despite limited resources and non-compliant patient population, we are striving to provide standard treatment to all breast cancer patients. Increase in sentinel lymph node biopsies instead of axillary clearance shows this expedition.